The Legal Intricacies of Illegal Pinjol and Pinjol - Rajin Sitepu (International Journal Labs, 2023)
Motivated by the many illegal pinjols that seem to be endless, even though thousands of them have been closed by the Government; The anxiety, anxiety, and anxiety experienced by victims of illegal pinjol, illegal pinjol which has clearly disturbed / hindered the growth of official pinjol, prompted a review of the problem of illegal pinjol and pinjol. From the review carried out, it is known that based on OJK Regulation Number 77 / POJK.01 / 2016 concerning Technology-Based Money Lending and Borrowing Services, lending must be held by an operator who is registered and has permission from the Financial Services Authority (OJK), its implementation must also follow OJK regulations. Loan operators who are not registered and have OJK permits, are illegal borrowers, who in offering and/or promoting their loans are carried out in ways that are not as promised, collection is carried out by means of threats and intimidation.